Pré-tratamentos alcalinos como facilitadores da obtenção de nanofibrilas de polpas celulósicas não branqueadas - Mendonça, Maressa Carvalho (2018)
The obtainment of cellulose nanofibrils by mechanical defibrillation results on high energy consumption, being thus a limiting factor for their production. Therefore, the objective of this work was to evaluate the effect of alkaline pre-treatments of unbleached cellulose pulps of eucalyptus and pinus, in order to facilitate the process of obtaining cellulose nanofibrils through mechanical defibrillation of the fibers and to reduce energy consumption in the defibrillator. Pretreatments were evaluated using NaOH at concentrations of 5% for 2 h of reaction, at 10% with reaction times of 1 h and 2 h; and a hybrid pretreatment with 5% / 16% NaOH / H 2 O 2 for 2 h. From the mechanical process, the nanofibrils were obtained using a defibrillator (SuperMasscolloider) and the morphology, chemical composition, turbidity and energy expenditure during the defibrillation process of the cellulosic fibers were evaluated for each pre-treatment. The results showed the influence of the removal of hemicelluloses in the extraction of nanofibrils as a function of the concentration and the time of reaction pretreatments increased the curvature of the fibers, mainly the pre-treatments with NaOH 10% 2 h due to the increase in the reaction time and the hybrid pre-treatment that removed lignin, allowing a greater action of the reagents in the fiber. The pretreatment NaOH 5% 2 h and 10% 1 h demonstrated a better result for obtaining the cellulose nanofibrils with less number of passages of the pulps in the defibrillator, being effective to facilitate the extraction of nanofibrils with less energy consumption and smaller diameters and more dispersed. Turbidity and decantation analyzes were performed in order to evaluate the suspensions regarding the degree of defibrillation and stability of defibrillated suspensions. The pretreatment NaOH / H2O2 did not present satisfactory results in the reduction of the energy consumption and the defibrillations for these pre-treatments presented inferior qualities to the pre-treatments of NaOH 5% 2 h and 10% 1 h.